Intramembrane Proton Binding Site Linked to Activation of Bacterial Pentameric Ion Channel - Wang, Hai-Long (American Society for Biochemistry and Molecular Biology, 2012)
Prokaryotic orthologs of eukaryotic Cys-loop receptor channels recently emerged as structural and mechanistic surrogates to investigate this superfamily of intercellular signaling proteins. Here, we examine proton activation of the prokaryotic ortholog GLIC using patch clamp electrophysiology, mutagenesis, and molecular dynamics (MD) simulations. Whole-cell current recordings from human embryonic kidney (HEK) 293 cells expressing GLIC show half-maximal activation at pH 6, close to the pK(a) of histidine, implicating the three native His residues in proton sensing linked to activation. The mutation H235F abolishes proton activation, H277Y is without effect, and all nine mutations of His-127 prevent expression on the cell surface. In the GLIC crystal structure, His-235 on transmembrane (TM) α-helix 2, hydrogen bonds to the main chain carbonyl oxygen of Ile-259 on TM α-helix 3. MD simulations show that when His-235 is protonated, the hydrogen bond persists, and the channel remains in the open conformation, whereas when His-235 is deprotonated, the hydrogen bond dissociates, and the channel closes. Mutations of the proximal Tyr-263, which also links TM α-helices 2 and 3 via a hydrogen bond, alter proton sensitivity over a 1.5 pH unit range. MD simulations show that mutations of Tyr-263 alter the hydrogen bonding capacity of His-235. The overall findings show that His-235 in the TM region of GLIC is a novel proton binding site linked to channel activation.